Simulasi Pengendalian Lift Menggunakan Manajemen Logika Fuzzy - Qasimi, Mehr Ali; Nashir, Asmatullah (Jurnal Teknik Informatika dan Sistem Informasi, 2024)
The use of a permanent magnet synchronous motor as an actuator in a ropeless elevator presents a number of difficulties that must be overcome for the system to be secure and stable. Detent force, one issue with stabilization systems, will be examined in terms of how well it functions under a fuzzy logic controller using a nonlinear test like changes in load and distance to obtain a policy suitable for application in the industrial sector or other human endeavors. The elevator technologies are designed to provide the necessary passenger floors while taking into account the highest standards of elevator performance and passenger pleasure. This work addresses the problem by developing an elevator group controller using a fuzzy algorithm. This project is designed to handle the necessary passenger traffic density while maintaining acceptable passenger waiting times by integrating a fuzzy controller into an elevator system. Within a set of fuzzy rules, three important linguistic variables are added to improve the performance of the elevator group. These consist of load capacity, priority, distance, and average waiting time (AWT). The necessity of floor priority is lessened when there is a great volume of passenger traffic; instead, the expected arrival time should be decreased. While the real elevator prototype is being programmed using a PIC microcontroller acting as a controller, the simulation was completed to visually verify the fuzzy system's priority. Thus, a set of ambiguous guidelines was developed based on real-world issues, primarily the reduction of waiting times and energy usage. The elevator controller will select which elevator will service which incoming hall request when a few are registered. In order to maximize efficiency for financial reasons, high-rise buildings and the ensuing large number of elevators they require provide a significant logistical challenge in terms of time and space conservation. In order to run the elevators properly, complex elevator group control systems are built.